If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + -40 = 7(-2nt + 2) Reorder the terms: -40 + 4n = 7(-2nt + 2) Reorder the terms: -40 + 4n = 7(2 + -2nt) -40 + 4n = (2 * 7 + -2nt * 7) -40 + 4n = (14 + -14nt) Solving -40 + 4n = 14 + -14nt Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '14nt' to each side of the equation. -40 + 4n + 14nt = 14 + -14nt + 14nt Combine like terms: -14nt + 14nt = 0 -40 + 4n + 14nt = 14 + 0 -40 + 4n + 14nt = 14 Add '40' to each side of the equation. -40 + 4n + 40 + 14nt = 14 + 40 Reorder the terms: -40 + 40 + 4n + 14nt = 14 + 40 Combine like terms: -40 + 40 = 0 0 + 4n + 14nt = 14 + 40 4n + 14nt = 14 + 40 Combine like terms: 14 + 40 = 54 4n + 14nt = 54 Reorder the terms: -54 + 4n + 14nt = 54 + -54 Combine like terms: 54 + -54 = 0 -54 + 4n + 14nt = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-27 + 2n + 7nt) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-27 + 2n + 7nt)' equal to zero and attempt to solve: Simplifying -27 + 2n + 7nt = 0 Solving -27 + 2n + 7nt = 0 Move all terms containing n to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 2n + 27 + 7nt = 0 + 27 Reorder the terms: -27 + 27 + 2n + 7nt = 0 + 27 Combine like terms: -27 + 27 = 0 0 + 2n + 7nt = 0 + 27 2n + 7nt = 0 + 27 Combine like terms: 0 + 27 = 27 2n + 7nt = 27 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 4/100= | | 4/109= | | 7/8=-2/3x-5 | | (2x-3)+(x+7)=42 | | -2=d-17/-1 | | 2x+3=112 | | 5a-3a=45-9 | | 25x-60=115 | | q^2+2g=323 | | 3x-20=1x | | 4v+8=26-2y | | 10x^3+11x^2-6x-2=0 | | 16(7c-1)-14=110c+16 | | 15.2=x+y | | 4t-3.5=12.5 | | x-20=1/2x-4 | | 52=xy | | -18+11z=18+13z | | 3.8x+8.93=-17.29 | | -(2-3(2.2))+2.2=9-2.2 | | 4(w+5)=-2(5w-8)+6w | | 12m=12+11m | | -(2-3(2.2))+2.2= | | 6a+19=44 | | 3.8+8.93=-17.29 | | 1a+6a-21b= | | -10p+11=-9p | | 16-6(-3+4)=28 | | -10+9+(-11)+(-29)= | | 6x=9-1 | | 34x+16+30x=52x+100 | | 3(8-x)+5=2x |